T-SPOT: A STEP AHEAD! - Sadia Hameed; Saira Sajid (Journal of University Medical & Dental College, 2020)
ABSTRACT Objective: To assess the utility of T-spot based Anti Tuberculosis therapy (ATT) in patients with Tuberculosis. Design of Study: Analytical Case Study. Setting: Department of Pathology, University Medical and Dental College (UMDC) and Meezan Laboratory, Faisalabad. Period: June, 2010 to December, 2010. Materials and Methods: All patients presenting to the Pathology Department at UMDC and Meezan Lab for T-spot testing were included in the study. A detailed history was taken and all cases were followed up. Results: Twenty patients presented for T-spot testing during the study period. Out of these 11(55%) were positive and 9 (45%) were negative. ATT was started in 10 out of the 11 positive patients. These patients were followed up and showed an improvement in their symptoms. Conclusions: T-spot test is a helpful tool for diagnosing the presence of TB infection. It has many advantages over Mantoux test especially in our setting where BCG vaccination is a major confounder.